Multi-functional concrete with recycled aggregates - Xu, Yidong; Jin, Ruoyu (Woodhead Publishing series in civil and structural engineering., 2023)
Multi-functional Concrete with Recycled Aggregates consists of chapters covering multiple aspects of sustainable concrete materials, inclusive of engineering, environmental, policy, and management factors. With contributing authors worldwide from a variety of disciplines bridged by the theme of sustainability of concrete, this book aims to provide an overview of existing research and practices of traditional recycled aggregate concrete; introduce the latest studies of high-performance concrete adopting recycled aggregates from C&D wastes; disseminate the latest findings of multifunctional recycled aggregate concrete by achieving the waste reuse while realizing other environmental sustainability goals; and link the multipurpose sustainable concrete technical development into the C&D waste management.